Bio-Fortification with Iron and Manganese for Enhanced Bunch Yield in 'Robusta' Banana through Direct Nutrient-Feeding - S C Kotur (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2015)
Enhancement of bunch weight together with bio-fortification with Fe and Mn was attempted in 'Robusta' banana by enriching with 0-1.25g bunch-1 each of FeSO4 (heptahydrate) and MnSO4 (monohydrate). Bunch yield and content of Fe and Mn in the pulp substantially increased by direct nutrient feeding of bunches with 7.5g each of urea and SOP besides 0.75g each of FeSO4 and MnSO4. The improved technique holds promise for combating anemia in humans by bio-fortification of banana with Fe besides supplemental Mn in diet.